Spin and pseudospin symmetries in the Dirac equation with central Coulomb potentials - De Castro, A. S. [UNESP]; Alberto, P. (American Physical Society (APS), 2012)
We analyze in detail the analytical solutions of the Dirac equation with scalar S and vector V Coulomb radial potentials near the limit of spin and pseudospin symmetries (i.e., when those potentials have the same magnitude and either the same sign or opposite signs, respectively). By performing an expansion of the relevant coefficients we also assess the perturbative nature of both symmetries and their relations to the (pseudo)spin-orbit coupling. The former analysis is made for both positive and negative energy solutions and we reproduce the relations between spin and pseudospin symmetries found before for nuclear mean-field potentials. We discuss the node structure of the radial functions and the quantum numbers of the solutions when there is spin or pseudospin symmetry, which we find to be similar to the well-known solutions of hydrogenic atoms. © 2012 American Physical Society.